Recruitment and retention of US South Asians for an epidemiologic cohort: Experience from the MASALA study. Issue 2 (27th May 2019) - Kanaya, Alka M.; Chang, Ann; Schembri, Michael; Puri-Taneja, Ankita; Srivastava, Shweta; Dave, Swapna S.; Vijayakumar, Evangeline N.; Qamar, Zubaida; Naik, Hemalatha D.; Siddiqui, Faiza; Kandula, Namratha R.
Abstract: Introduction: There are few longitudinal studies about South Asians (SAs) and little information about recruitment and retention approaches for this ethnic group. Methods: We followed 906 SAs enrolled in the Mediators of Atherosclerosis in South Asians Living in America (MASALA) cohort for 5 years. Surviving participants were invited for a second clinical exam from 2015 to 2018. A new wave of participants was recruited during 2017–2018. We assessed the yields from different methods of recruitment and retention. Results: A total of 759 (83%) completed the second clinical exam, and 258 new participants were enrolled. Providing a nearby community hospital location for the study exam, offering cab/shared ride reimbursement, and conducting home visits were the most effective methods for enhancing retention. New participant recruitment targeted women and individuals with lower socioeconomic status, and we found that participant referrals and active community engagement were most effective. Mailing invitational letters to those identified by electronic health records had very low yield. Conclusion: Recruitment and retention strategies that address transportation barriers and increase community engagement will help increase the representation of SAs in health research.